1974
DOI: 10.1507/endocrj1954.21.173
|View full text |Cite
|
Sign up to set email alerts
|

Radioimmunoassay of Parathyroid Hormone in Human Plasma and Tissue Using Commercially Available Antiserum and Modified Iodination

Abstract: SynopsisThe human PTH radioimmunoassay has been developed by use of bovine PTH and anti-bovine PTH antiserum, both of which were commercially available. The iodination process was modified as to use acid solution resulting in the more stable 125I-PTH. However, the PTH radioimmunoassay employed this antiserum with 125I-bovine PTH revealed that the N-terminal portion of PTH molecule was reactive only slightly in this system, indicating that most of PTH determined by this radioimmunoassay might be an biologically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1974
1974
1984
1984

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The accumulation of aluminium in patients with chronic renal failure may occur as a result of three factors, namely: (1) renal mass reduction may induce aluminium accumula tion, since the kidney is the main route for excretion of aluminium in humans [8,23]; (2) long-term ingestion of an aluminium-containing phosphate binder could be a factor for aluminium accumulation [1,32]; (3) dialysis itself might be an important cause of aluminium accumulation [15,22,30]. Previously, we reported that an aluminium-containing phosphate binder had little effect on serum aluminium concentration in undialyzed and dialyzed patients [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The accumulation of aluminium in patients with chronic renal failure may occur as a result of three factors, namely: (1) renal mass reduction may induce aluminium accumula tion, since the kidney is the main route for excretion of aluminium in humans [8,23]; (2) long-term ingestion of an aluminium-containing phosphate binder could be a factor for aluminium accumulation [1,32]; (3) dialysis itself might be an important cause of aluminium accumulation [15,22,30]. Previously, we reported that an aluminium-containing phosphate binder had little effect on serum aluminium concentration in undialyzed and dialyzed patients [34].…”
Section: Discussionmentioning
confidence: 99%
“…Serum iPTH concentra tion was determined by a double antibody radioimmunoassay tech nique using antibovine anti-iPTH serum (Wellcome Co. Ltd., Eng land), as described by Tanaka et al [32], Bovine PTH (Wilson Lab., USA) was used as a standard material.…”
Section: Methodsmentioning
confidence: 99%
“…Plasma HDL-cholesterol was measured by the heparin-Mn++ precipitation method [13], Plasma lecithin-cholesterol acyltransferase (LCAT) activity was measured according to the method of Nagasaki and Akannma [14], its activity being expressed as units, i.e. free cholesterol umol/ml/h at 37 C. Parathyroid hormone (PTH), which is likely to suppress the lipo protein lipase activity and, on the other hand, to stimulate lipolysis and release of free fatty acids into the bloodstream, was measured by radioimmunoassay [15].…”
Section: Methodsmentioning
confidence: 99%
“…Plasma PTH levels were determined by the radioimmunoassay as reported previously (Tanaka et al, 1974). Calcium (Ca) and magnesium (Mg) were determined by atomic absorption spectrophotometry and phosphate (P) by the method of Goldenberg and Fernandez (Goldenberg and Fernandez, 1966).…”
Section: Methodsmentioning
confidence: 99%